Modified Shock Index is a Predictor for 7-Day Outcomes in Patients With STEMI - Shangguan, Qing; Xu, Jing-song; Su, Hai; Li, Ju-xiang; Wang, Wen-ying; Hong, Kui; Cheng, Xiao-shu (The American journal of emergency medicine, 2015)
The aim of this study was to compare the predictive values of modified shock index (MSI) and shock index (SI) for 7-day outcome in patients with ST-segment elevation myocardial infarction (STEMI). This retrospective study included 160 consecutive patients with STEMI and emergency percutaneous coronary intervention. The blood pressure (BP) and heart rate (HR) measured at emergency department were used to calculate SI (HR/systolic BP) and MSI (HR/mean artery pressure). The major adverse cardiac events (MACE) included all-cause mortality, life-threatening arrhythmias, cardiogenic shock, and Killip class within 7 days. Forty-nine patients had increased MSI (≥1.4), whereas 72 had increased SI (≥0.7). Except the parameters on BP and HR, other parameters were similar between the normal and increased SI groups. However, the increased MSI group had significantly higher age (69.0 ± 13.0 years vs 63.9 ± 12.9 years, P = .025) than the normal MSI group. The 7-day all-cause mortality was 8.8%, and MACE rate was 24.4% in this study. Both increased SI and increased MSI predicted higher MACE rates. However, the odds ratios of increased MSI for all-cause mortality (6.8 vs 3.4), cardiogenic shock (3.0 vs 1.6), life-threatening arrhythmias (9.1 vs 4.6), and MACE (6.8 vs 3.4) were higher than those of increased SI. Modified shock index and SI were independent factor for MACE, but the odds ratio of MSI was higher than of SI (3.05 vs 1.07). Both SI and MSI in emergency department could predict the all-cause mortality and MACE rates within 7 days in patients with STEMI, but MSI may be more accurate than SI.